Outcome of video-assisted thoracoscopic implantation of epicardial left ventricular leads with visual targeting for cardiac resynchronization therapy. (4th December 2019) - Stauber, Annina; Tanner, Hildegard; Noti, Fabian; Roten, Laurent; Seiler, Jens; Lam, Anna; Medeiros-Domingo, Argelia; Servatius, Helge; Tran, Van Nam; Carrel, Thierry; Weber, Alberto
Abstract: : OBJECTIVES: Our goal was to analyse the implantation and outcome of thoracoscopic epicardial leads after a failed endovascular approach or follow-up (FU) complications after endovascular implantation. METHODS: We reviewed the records of patients with failed endovascular left ventricular (LV) lead placement or complications during FU, who were subsequently referred to cardiac surgeons for treatment with thoracoscopic LV lead implantation. We analysed the reasons for endovascular failure; the indications for the surgical procedures; and the clinical, echocardiographic and device FU results. RESULTS: Between 2010 and 2013, a total of 23 patients were included. Among them, 17 of the patients had no previous cardiothoracic surgery, 13 (76%) had successful video-assisted thoracoscopy (VAT) LV lead implantation, 3 (18%) had a conversion to thoracotomy and 1 (6%) failed. Of the 6 patients with prior cardiothoracic surgery, 2 (33%) had VAT only, 3 (50%) had primary thoracotomies and 1 (17%) had a conversion. Two major complications occurred. The reasons for LV endovascular lead failure were subclavian vein occlusion ( n  = 2), implant failure ( n  = 13) and complications during the FU period ( n  = 8). FU information was available for 20 patients: 17 (85%) had improved symptoms. The median FU period was 33 months. A total of 78% of patients were in New York Heart Association (NYHA) functional class III–IV before the operation; 30% were in NYHA functional class III–IV at the last FU examination. The left ventricular ejection fraction increased from 25% before surgery to 31% at the last FU examination. Overall, sensing and pacing threshold values remained stable over time. In 1 patient, lead revision was necessary due to an increase in the pacing threshold. CONCLUSIONS: VAT implantation of LV leads had an excellent response rate with an improvement in NYHA functional class and left ventricular ejection fraction. The lead measurements were mainly stable over time.